INTEGRASI SAINS DENGAN AGAMA DAN PEMIKIRAN PENDIDIKAN ISLAM PERSPEKTIF NIDHAL GUESSOUM - Husni Mubarok; Amril Mansur (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
The aim of this research is to determine the integration of science with religion and Islamic educational thought from Nidhal Guessoum's perspective. The research method used is library research. The results of the research show that: a) Nidhal Guessoum's work consists of approximately 8 book titles, one of which is quite popular in Indonesia, namely Islam's Question Reconciling Muslim Tradition and Modern Science (2011), with the Indonesian title